Cumby, Art. An interview about growing up in Heart's Content. - Wilson, Lisa (2013)
Art Cumby introduces himself; Family history--father worked in lumber woods, mother worked at a telephone switchboard till 1966; Father eventually worked as maintenance for Western Union; Went to school at Lakeview High; Description of the school; 4:30 - After school activities; Gardening, mother grew 42 sacks of potatoes one year; 5:40 - Everybody was friends back then; Always wanted to come back to Heart’s Content; Story of his house--Bobby’s Uncle Bill’s house (getting photograph); More family information; 10:23 - Cumby one of the oldest family names in Heart’s Content (1800s); Unmarked graveyard in the oral history; Wooden boat discovery; 15:00 - Salvation Army single gravesite; Ancestors in the different cemeteries; The role of religion; First left H.C. at age 17; Working for town council; 20:00 - Future of Heart’s Content; 1926 population of 3000, now 350; Heritage promotion and lost traditions/information; 24:10 - Losing skills; Bringing people in for work; Youth and technology; 28:00 - Collective child-rearing; Trouting in the country as a boy; 30:00 - effect of confederation on women; Birth rates in Newfoundland; When Art and Ruth got married; Buildings taken for granted; Community improvements and water tank; 34:30 - Four water tanks in town; Bailey first wireless operator from NL; Houses that have been ‘cut back’; Change in the community; Steamers used to go up ‘the brook’; 38:30 - Cannon found in a chimney; Staying away from the brook; Skating on the pond back then; 41:50 - Fairy story about the Glambrook; Stories about the Glambrook and how people perished in the 1880s; Halfway house 7 km between Heart’s Content and Victoria; People didn’t have cameras; Moose hunting in H.C.; Passing along hunting traditions; Property taxes in NL; Work his mother did; 53:00 - H.C. segregated in the past; 55:50 - Need for young people in town; Art’s father couldn’t read or write; Showing old photographs; Father when he was in forestry; Further family information.